Media Freedom and Censorship: A Comparative Case Study of Media Freedom under Previous and Current Taliban Governments - Alokozay, Naveedullah (Program Studi Politik Islam Universitas Islam Negeri Raden Fatah Palembang, 2024)
The study compares media freedom and censorship under the present Taliban regime in Afghanistan to that under the previous Taliban rule (1996–2001). It looks into how the two regimes' changes to media laws and regulations affected journalists and media organizations. The study questions are concerned with the variations in media freedom, certain types of censorship, and the influence of technology development on media freedom. The study uses a comparative case study methodology to examine the legal system, media regulation, and public access to media coverage in the past and present. Collecting data entails compiling facts from academic research, human rights reports, media observers, and news articles. The study indicates that Taliban regime has become flexible in their policies toward media freedom in contrast to total ban in Taliban’s initial regime on media freedom. The study's importance rests in giving policymakers, human rights organizations, and media professionals’ information on how media freedom was affected by the Taliban's control. This will help them support that Freedom and fight for journalists' rights in Afghanistan.